Sociocultural and Historical Perspectives on Diversity in Spain - Lénárt, András (Ethnographica et Folkloristica Carpathica, 2024)
The image of Spain in the 21st century is defined by the coexistence of the descendants of different peoples who have arrived in the region over the past centuries and decades. Since prehistoric times, the history of the Iberian Peninsula has been marked by interactions between the groups that settled there; sometimes these relationships have involved a certain type of subordination and domination (for example, conqueror versus conquered), and at other times they have been characterised by the peaceful or conflictual coexistence of different societies. Thus, immigration, coexistence and assimilation have always been fundamental to the social and cultural life of Spain. To this day, cultural historians and philosophers have not been able to agree on whether the diversity of society has been an advantage or a disadvantage for the development of Spain. In this article, I will examine the approaches to this social and cultural diversity in different historical periods and the basic arguments used by scholars and scientists to support their beliefs. In analysing the issue, we look at prominent works and authors in Spanish cultural history, searching for and comparing possible arguments. We try to answer the question to what extent the search for homogeneity or diversity has been part of the Spanish self-definition in a given historical period.